Coping with College and Inflammatory Bowel Disease: Implications for Clinical Guidance and Support. Issue 9 (7th August 2014) - Schwenk, Hayden T.; Lightdale, Jenifer R.; Arnold, Janis H.; Goldmann, Donald A.; Weitzman, Elissa R.
Abstract : Background: Studies have shown that young adults with chronic diseases, including inflammatory bowel disease (IBD), experience greater difficulty during the transition to college, reaching lower levels of educational attainment and reporting greater levels of perceived stress than their otherwise-healthy peers. We performed a qualitative study to better understand how underlying illness shapes the college experience for patients with IBD and how the college experience, in turn, impacts disease management. Methods: Fifteen college students with IBD were recruited from the Boston Children's Hospital Center for IBD. We conducted an approximately 1 hour semistructured qualitative interview with each participant, and the interviews were thematically analyzed after an iterative and inductive process. Results: Four primary themes were identified: (1) The transition experience of college students with IBD is shaped by their health status, perceived readiness, and preparedness, (2) Elements of the college environment pose specific challenges to young adults with IBD that require adaptive strategies, (3) College students with IBD integrate their underlying illness with their individual and social identity, and (4) College students navigate health management by conceptualizing themselves, their families, and providers as serving particular roles. Conclusions: For young adults with IBD, college is a proving ground for demonstrating self-care and disease management practices. Future initiatives aimed at this population should recognize the evolving roles of patients, parents, and providers in disease management. Increased attention should also be paid to the promotion of patient's self-management and the unique challenges of the structural and psychosocial college environment.